Genetic analysis for seed yield and its contributing traits in linseed (Linum usitatissimum L.): GENETIC ANALYSIS FOR SEED YIELD AND ITS CONTRIBUTING TRAITS IN LINSEED - ACHILA SINGH; NALINI TEWARI (Journal of Oilseeds Research, 2014)
An experiment was conducted to study the gene action in linseed through diallel analysis using 11 parents and their 55 crosses. Analysis of variance showed highly significant differences among the genotypes for all the traits. Graphical analysis displayed non-additive gene action playing major role in the expression of all the attributes. Components of variance revealed the presence of both additive as well as dominance component for days to 50 per cent flowering, days to maturity, plant height, number of seeds/capsule, 100-seed weight, seed yield/plant, harvest index and oil content. Average degree of dominance ( 1/Ď) 0.5 exhibited over dominance for all the traits except test weight. High estimates of heritability with high genetic advance were reported for 100-seed weight whereas high heritability with low genetic advance was observed for days to maturity and oil content. Low heritability with high genetic advance was recorded for number of capsules/plant and primary branches/plant. Moderate heritability with high genetic advance was noticed for seed yield/plant.